2001
DOI: 10.1177/08959374010150012001
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Signals during Odontoblast Differentiation

Abstract: Odontoblast terminal differentiation occurs according to a tooth-specific pattern and implies both temporospatially regulated epigenetic signaling and the expression of specific competence. Differentiation of odontoblasts (withdrawal from the cell cycle, cytological polarization, and secretion of predentin/dentin) is controlled by the inner dental epithelium, and the basement membrane (BM) plays a major role both as a substrate and as a reservoir of paracrine molecules. Cytological differentiation implies chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 56 publications
1
66
0
5
Order By: Relevance
“…The differentiation of amelo-and odontoblasts and subsequent dentin and enamel formation is regulated by epithelial-mesenchymal interactions between the dental papilla and inner dental epithelium cells and involves the activity of signaling molecules (for review, see Lesot et al, 2001). We found that in addition to being expressed in the developing mandibular bone, Dkk1 was prominently up-regulated in the preodontoblasts and the expression continued in the secretory odontoblasts.…”
Section: Possible Roles For Dkks In Crown Calcificationmentioning
confidence: 70%
“…The differentiation of amelo-and odontoblasts and subsequent dentin and enamel formation is regulated by epithelial-mesenchymal interactions between the dental papilla and inner dental epithelium cells and involves the activity of signaling molecules (for review, see Lesot et al, 2001). We found that in addition to being expressed in the developing mandibular bone, Dkk1 was prominently up-regulated in the preodontoblasts and the expression continued in the secretory odontoblasts.…”
Section: Possible Roles For Dkks In Crown Calcificationmentioning
confidence: 70%
“…The different induction stages that precede the morphogenesis and differentiation of the teeth result from reciprocal interactions among stomodeal epithelial cells and mesenchymal cells derived from neural crests (ectomesenchyme) (12,13). The identification of numerous growth differentiation factors (14)(15)(16)(17), transcription factors (18)(19)(20)(21) and molecules of adhesion (22)(23)(24) expressed in the course of the development of the tooth have revealed associations of multiple genes with tooth morphogenesis. Studies on the functions of signals and tissue interactions in cultured tissue explants and in mutant mouse embryos have revealed inductive signaling and hierarchies in downstream transcription factors (25).…”
Section: Introductionmentioning
confidence: 99%
“…These findings have subsequently been extended, and it has been postulated that TGF-␤s (TGF-␤1 and -␤3), derived from the enamel organ and immobilized and activated by components of the basement membrane, induce odontoblast differentiation. Odontoblasts, in turn, then express TGF-␤, which acts in an autocrine manner to stimulate the secretion of predentin and dentin (Lesot et al, 2001). This proposal is consistent with observations showing the presence of TGF-␤ isoforms in dentin matrices (Cassidy et al, 1997) and both TGF-␤ isoforms and T␤R-I and T␤R-II in odontoblasts (Sloan et al, 1999(Sloan et al, , 2000.…”
Section: (C) Tooth Morphogenesismentioning
confidence: 99%